2018
DOI: 10.1063/1.5037992
|View full text |Cite|
|
Sign up to set email alerts
|

Fast water flow through graphene nanocapillaries: A continuum model approach involving the microscopic structure of confined water

Abstract: Water inside a nanocapillary becomes ordered, resulting in unconventional behavior. A profound enhancement of water flow inside nanometer thin capillaries made of graphene has been observed [B. Radha et.al., Nature (London) 538, 222 (2016)]. Here we explain this enhancement as due to the large density and the extraordinary viscosity of water inside the graphene nanocapillaries. Using the Hagen-Poiseuille theory with slippage-boundary condition and incorporating disjoining pressure term in combination with resu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
104
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(120 citation statements)
references
References 52 publications
16
104
0
Order By: Relevance
“…Hydrated graphene interfaces are of particular interest due to posible applications, including desalination [34,35,36,37,38] decontamination [39,40,41], energy storage [42,43], heterogeneous catalysis, graphene exfoliation and transferring [44,16]. Graphene confinement enriches the complex phase diagram of bulk water in simulations [45,46,47,48,49,50,51,52,53,4,54,55] and experiments [56,57,58,59], and changes the water dynamics and structure, as seen numerically [60,61,62,63,8,64,65,66,5,6,67,68,69] and in laboratories [7,70,71].…”
Section: Introductionmentioning
confidence: 99%
“…Hydrated graphene interfaces are of particular interest due to posible applications, including desalination [34,35,36,37,38] decontamination [39,40,41], energy storage [42,43], heterogeneous catalysis, graphene exfoliation and transferring [44,16]. Graphene confinement enriches the complex phase diagram of bulk water in simulations [45,46,47,48,49,50,51,52,53,4,54,55] and experiments [56,57,58,59], and changes the water dynamics and structure, as seen numerically [60,61,62,63,8,64,65,66,5,6,67,68,69] and in laboratories [7,70,71].…”
Section: Introductionmentioning
confidence: 99%
“…The phase behavior of two-dimensional (2D) ice is the subject of recent experimental and theoretical interest, and is still controversial [1][2][3][4][5][6][7][8]. Recently the report of the observation of monolayer, bilayer, and trilayer ice using transmission electron microscopy [1] was challenged [9]; however, several theoretical studies based on both classical force fields and ab initio simulations revealed the exciting possibility of exploring 2D-ice structures at specific conditions [2,3,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…The density of water in the channel after filling is reported as the number of water molecules per unit area ( ρ 2D = n w / L x / L y ). Use of an area density avoids having to define an effective nanochannel height, 62 which for very narrow nanochannels depends strongly on the arbitrary volume occupied by the atoms at the edge of each wall. The area densities, provided in Table 1, increase with nanochannel height from 11.0 molecules per nm 2 for n = 1 to 67.3 molecules per nm 2 for n = 6, due to the increasing number of water layers that can be accommodated.…”
Section: Resultsmentioning
confidence: 99%